Experimental investigation on energy saving potential of smart HVAC unit. Issue 4 (19th May 2019) - Irudaya Raj, V. Dickson; Logesh, K.; Vasudevan, A.; Bhavesh Nishant, Basant; Deepak, Aruru; Arvind, T.
ABSTRACT: It is well known that 'the energy can't be created but could be saved' and the energy resources are depleting at an alarming rate over the decades. The HVAC unit consumes 1/5th of the World's electrical power consumption. Over the years several modifications have been made on the HVAC unit to save energy. This study implements the machine-to-machine interaction through Internet of things which reduces the human effort. The proposed system utilises the smart power controlling and modifying feedback systems from mobile phones integrated with human motion detectors. Due to the accurate feedback system, the room temperature can be maintained within the range of ±0.3°C. The experiment shows an interesting result that the power consumption of compressor can be reduced by 45% using the smart control HVAC unit. The client can also control the system through a web server which controls the actuators.